Frequency of Persistent Smoking Among Patient Undergone Percutaneous Coronary Intervention (PCI) at Tertiary Care Hospital - Saher, Shafaq; Ahmed, Faisal; Sikandar, Fazila; Abubakar, Sadia; Maream, Sana (Indus Journal of Bioscience Research, 2025)
Background: Tobacco smoking is a major modifiable risk factor for coronary artery disease and is strongly associated with adverse cardiovascular outcomes. Although percutaneous coronary intervention effectively restores coronary blood flow in patients with acute coronary syndrome, continued smoking after intervention significantly reduces its long-term benefits and increases the risk of recurrent cardiac events. Objective: To determine the frequency of persistent smoking among patients undergone percutaneous coronary intervention (PCI) at a tertiary care cardiac center. Methods: This was a descriptive, cross-sectional study conducted at the Department of Cardiology, Liaquat National Hospital & Medical College, Karachi, from 14 February 2025 to 14 May 2025. A total of 178 patients who had undergone percutaneous coronary intervention (PCI) for acute coronary syndrome were included. Results: Persistent smoking was observed in 68 patients (38.2%), while 110 patients (61.8%) successfully quit smoking after PCI. Higher rates of persistent smoking were noted among younger patients aged 30–44 years (50.0%), males (42.6%), obese individuals (49.2%), and patients with diabetes mellitus (52.2%) and dyslipidemia (47.7%). Heavy smokers consuming more than 20 cigarettes per day showed the highest persistence rate (56.8%). Multivariable analysis identified male gender (adjusted OR 2.14), age